PENGARUH BUDAYA ORGANISASI, MOTIVASI, DAN KEPUASAN KERJA TERHADAP DISIPLIN KERJA DOSEN TETAP DI MH THAMBRIN - Moh Muhidin Mulyana; Sri Yanthy Yosepha (Prodi Magister Manajemen Universitas Dirgantara Marsekal Suryadarma, 2023)
This research has five main objectives: First, to prove and analyze the influence of organizational culture towards work discipline; Second, to prove and analyze the influence of motivation towards work discipline; third, to prove and analyze the influence of job satisfaction towards work discipline; Fourth, to prove and analyze the influence of organizational culture towards the job satisfaction; and Fifth, to prove and analyze the influence of motivation towards the job satisfaction. The research was conducted using a quantitative approach, using a survey method through the distribution of questionnaires. This research involved 83 permanent lecture permanent lecturer at the university of MH. Thamrin as our research sample. Path analysis was used to test and analyze relationship among the research variables. Measurements in the study were carried out by giving the value of each question item from all variables, the size of the value given in each statement using a